1991
DOI: 10.1111/j.1523-536x.1991.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

How Frequently Are Home Pregnancy Tests Used? Results from the 1988 National Maternal and Infant Health Survey

Abstract: Many women use commercially available home pregnancy tests to determine their pregnancy status before seeking professional health care. Despite the increasing popularity of these products, no national estimates have been reported to date on their frequency of use. We analyzed available data from the 1988 National Maternal and Infant Health Survey to determine the frequency of use of home pregnancy tests during recent pregnancies of women of varying sociodemographic backgrounds. Approximately 33 percent (N = 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…These findings are consistent with those of 3 older studies, 4,5,7 which reported home pregnancy test use rates of 17.2% among college health care clinic patients and 15% to 31% among pregnant adolescents. The prevalence of home pregnancy test use may have been underestimated in the current study because the data were from clinic-based samples.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are consistent with those of 3 older studies, 4,5,7 which reported home pregnancy test use rates of 17.2% among college health care clinic patients and 15% to 31% among pregnant adolescents. The prevalence of home pregnancy test use may have been underestimated in the current study because the data were from clinic-based samples.…”
Section: Discussionsupporting
confidence: 83%
“…Home pregnancy test use has been examined for college students and pregnant adolescents and women, 4,5 but use of the tests in the general adolescent population is unknown. The purpose of this study was to estimate the prevalence of home pregnancy testing among adolescents in clinic populations.…”
mentioning
confidence: 99%
“…Preliminary analyses using NMIHS pretest or provisional data have been conducted in the following areas: information from unmarried mothers (7); diagnostic imaging and fetal monitoring (12); medical devices used during pregnancy, delivery, and infant care (13); weight gain during pregnancy (14); infant feeding (15); WIC participation (16); insurance coverage (17); depression and birth outcome (18); home pregnancy testing (19); and birth outcomes of African-American women (20). These and other reports will be completed using the full data sets.…”
Section: Resultsmentioning
confidence: 99%
“…2 Data from several studies in the United States show that more than one third of women have used an HPT. [3][4][5][6] Convenience, privacy, speed of obtaining results, and ability to determine pregnancy status prior to visting a health professional are some of the underlying factors attributed to the popularity of HPTs.…”
Section: Introductionmentioning
confidence: 99%